The Correlation of Smartphone Use with Emotional Intelligence of Students at the Alma Ata University Students’ Islamic Boarding School - Dian Elok Faiqoh; Misyroh Akhmadi (Eshraq: Journal of Islamic Studies, 2026)
This study aims to determine the level of emotional intelligence and analyze the correlation between smartphone usage and emotional intelligence of students at the Student Islamic Boarding School (PPM) of Alma Ata University. The background of the study is based on the rapid development of communication technology, which has a significant impact on students. Uncontrolled smartphone usage has the potential to trigger individualistic attitudes and reduce social sensitivity (phubbing) (Sulastri et al., 2023). The sampling technique used in this study was simple random sampling. The research method used was a quantitative correlational approach, with data collection through observation and questionnaires distributed to 78 respondents. Data analysis was performed using a simple linear regression test using SPSS 20.0 for Windows software. The results showed that the majority of students (92.31%) had moderate or controlled smartphone usage, while the majority had moderate (84.62%) to high (15.38%) emotional intelligence levels. The correlation test found a significance value of 0.023 (p < 0.05), indicating a significant but weak positive correlation between smartphone usage and emotional intelligence, with a contribution of 6.6%. This study concluded that wise smartphone use for productivity can support the stability of students' emotional intelligence, although most other emotional intelligence factors are influenced by variables outside the study.